Reinterpretasi Ayat-ayat Kekerasan: Upaya Membangun Islam Moderat - Aniqoh, Lina (MAGHZA: Jurnal Ilmu Al-Qur'an dan Tafsir, 2018)
This paper seeks to elaborate on the textual interpretation of Q.S Muhammad verse 4 and Q.S at Taubah verse 5. These two verses are often employed by the extremist Muslim groups to legitimize their destructive acts carried out on groups considered as being infidels and as such lawfully killed. The interpretation was conducted using the double movement hermeneutics methodology offered by Fazlur Rahman. After reinterpretation, the two verses contain moral values, namely the war ordered by God must be reactive, fulfill the ethics of "violence" and be the last solution. Broadly speaking, the warfare commanded in the Qur'an aims to establish a benefit for humanity on the face of the earth by eliminating every crime that exists. These two verses in the contemporary socio-historical context in Indonesia can be implemented as a basis for combating the issue of hoaxes and destructive acts of extremist Muslim groups. Because both are crimes and have negative implications for the people good and even able to threaten the unity of mankind.